TOURISM AFFAIR MANAGEMENT WITH COLLABORATIVE GOVERNANCE APPROACH: TOURISM AFFAIRS MANAGEMENT STUDIES IN SLEMAN REGENCY, YOGYAKARTA - Muchamad Zaenuri, Sumartono (IJMAS, 2015)
This paper describes the consequences of the decentralization policy in Indonesia towards the form of tourism affairs which is implemented by the Local Government of Sleman Regency. The fundamental theory of the tourism affairs division is an area with a division of power-sharing approach. Tourism affairs cannot be carried out only by the local governments themselves. They have a limited capacity that need co-operation with the private sector and the community. Formal tourism affairs in Sleman were fairly well implemented. However, it still has some treaties. Thus, they need an alternative solution to the constraints by using collaborative governance model which proposed by the researcher in this paper